Advances in Data Mining. Applications and Theoretical Aspects 11th Industrial Conference, ICDM 2011, New York, NY, USA, August 30 - September 3, 2011. Proceedings - Perner, Petra (Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 11th Industrial Conference on Data Mining, ICDM 2011, held in New York, USA in September 2011. The 22 revised full papers presented were carefully reviewed and selected from 100 submissions. The papers are organized in topical sections on data mining in medicine and agriculture, data mining in marketing,  data mining for Industrial processes and in telecommunication, Multimedia Data Mining, theoretical aspects of data mining, Data Warehousing, WebMining and Information Mining.